English-Indonesian and Indonesian-English Code Switching Used by the Teachers in Teaching-Learning English at the 11th Grade of SMAN 2 Mataram in the Academic Year of 2022/2023 - Hafsah Hadhanah; Amrullah; Muh. Isnaini (Journal of English Education Forum (JEEF), 2023)
Language is the most important component of the lives of all individual’s life. People will be able to communicate with one another more conveniently and effectively if they use language. People speak a variety of languages for a variety of reasons. It could be anywhere, including home, work, school, or campus. In a communication process, people may switch language codes, such as the English language, to the Indonesian language or vice versa. This research aimed to identify and describe the types and functions of English-Indonesian and Indonesian-English code switching used by the teachers in teaching-learning English at the 11th Grade of SMAN 2 Mataram. This research concentrates on two English teachers who currently teach students in the 11th grade who are majoring in science during the academic year 2022/2023. This study employed a descriptive qualitative methodology, and observation was the primary data collection method. A pre-observation class will be held as the first step in this research project to choose the topic. From the results, during classrooms, the first English teacher’s utterances caused sixty-seven codes switching and the second English teacher’s utterances caused forty-six codes switching. While for the functions, both English teachers only used five out of six functions of code switching. The research results show that the type of code switching mainly used by the English teachers is inter-sentential code switching and the function used mainly by English teachers is managing class.